Antileucoprotease in the developing fetal lung. - Willems, L N (1988)
The distribution of antileucoprotease in the lungs of 25 fetuses of 9-40 weeks' gestation was studied with monoclonal antibodies and an indirect immunoperoxidase technique. Antileucoprotease was detected from 16 weeks in submucosal glands and collecting ducts in the trachea and main and lobar bronchi: it was also found in the surface epithelium of the trachea at 20 weeks, in main and lobar bronchi at 20 weeks, and in smaller bronchi at 20-25 weeks. Non-ciliated cells containing antileucoprotease were observed in the bronchiolar epithelium at 36 and 40 weeks. The results of this study indicate that antileucoprotease is available from birth. It may therefore form part of the first line of defence of the lung.